PERSISTÊNCIA DE Metarhizium anisopliae spp NO SOLO SOB DIFERENTES CONDIÇÕES DE TEMPERATURA E UMIDADE - Diana Mendonça Silva Guerra (Revista Caatinga, 2009)
The fungi entomopathogenic are actually objects of works according to their importance in the ecological system. This work analysed the persistence of Metarhizium anisopliae var. anisopliae and M. anisopliae var. acridum, under different conditions of temperature and humidity, in the period of September to December. After inoculation on soil the fungi were submitted to four different treatments: environment temperature and 25% of humidity; environment temperature and 75% of humidity; 28º C and 25% of humidity; 28º C and 75% of humidity, during 120 days. The results show that M. anisiopliac var. anisopliae presented the most recuperation in the treatment at 28º C and 75% of humidity (P > 0,05) in 30 days and maintained a positive conditions on soil for 120 days of experiment. The same did not happen to M. anisopliae var. acridum that, during the whole process of observation and controll the colonies recuperation avoiding its persistence on soil, during the 120 days of experiment.